Urgensi Literasi Digital untuk Generasi Milenial di Era Society 5.0 - Tatik Purwaningsih; Nurul Hidayat; Arnold Surya Nugroho; Ria Restina Robiyanti (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
The current era of society 5.0 is a challenge in itself with the development of digitalization issues that impact all aspects of life. Society is so spoiled by media and technology. However, there are positive and negative impacts in today's rapid technological advances such as hoax news, cyber bullying and body shaming. The purpose of this community service activity is to mitigate negative impacts and provide an understanding of how to use the internet in a good and healthy way through digital literacy. The methods used are lectures, question and answer and use the pretest as a measuring tool. The results of this study are that the millennial generation is very familiar with using current applications, but they don't care about their own security in cyberspace. In addition, they also do not know their privacy rights when surfing the internet and there are still many who cannot use social media wisely. Hopefully it is hoped that the digital literacy training from this community service program will have a significant impact on the importance of maintaining data privacy and how to wisely use social media.